Uma intervenção matemática numa escola de tempo integral da periferia de Fortaleza: traçando um perfil nutricional dos estudantes do ensino médio. - Silva, Fábio Martins (2024)
This work proposes to analyze the nutritional performance of students in the initial grades from highschool. To do this, weight, height, age, in addition to a set of data that makes up a standard anamnesis questionnaire. The justifications for this work is to provide relevant data on the students' nutritional situation, their lifestyle, as well as your metabolic profile. Furthermore, the school will be able to collaborate with the alignment of physical education work, targeting students who need it most and contribute to a better quality of life for these students. In the future, the school may propose an intervention in the menu, as it has information about caloric consumption at rest. You objectives are to present a nutritional profile of students from Fortaleza City Hall and who entered the first year of high school in 2022. Present a study of the rate of body mass by category of all first-year high school students. A methodology consists of using data collection, organization and analysis as a method from of a sample space with first-year high school students. Data collection was carried out with a standard printed anamnesis questionnaire carried out between August and September 2022, between 8 am and 11 am, which contained objective and subjective questions about the eating routine at school, such as number of meals, weight, height, hours of sleep and body mass index which makes up the nutritional profile of students, aged between 16 and 19 enrolled in first year of high school, totaling a sample of 81 students, 44 of whom were boys and 37 girls, which corresponds to 30% of the total number of students enrolled. The organization and analysis was made with the Microsoft Excel tool, a spreadsheet editor produced by Microsoft that uses the Windows operating system. Based on the organized data, the basal metabolism will be calculated suggesting the student energy expenditure based on BMR using the Harris & Benedict equation. With based on the information collected, a spreadsheet was created in Microsoft Excel containing information about name, sex, weight, height, BMI, BMR as well as other nutritional data such as the regularity of daily meals and weekly physical activity. Considering the context socioeconomic status of the community in which the school is located, a lack of nutrition in students, a crucial portion of students who go hungry in their homes, often do not have the family structure to prepare their breakfast in the morning. first meal.